Konstruksi Klausul Tanggung Jawab Sosial Lingkungan Pada Akta Perubahan Anggaran Dasar Perseroan Terbatas Di Bidang Sumber Daya Alam: Construction of the Clause of Environmental Social Responsibility in the Deed of Amendment to the Articles of Association of Limited Liability Companies in the Sector of Natural Resources - Nayu Triska Wulan Dari; Martyani, Eka (Universitas Adiwangsa Jambi, 2023)
Article 74 of the Company Law requires companies that carry out business activities in the field of and/or related to natural resources to carry out Environmental Social Responsibility, in which these obligations are budgeted and calculated as Company costs by taking into account propriety and fairness. Which budgeting is carried out based on the company's work plan which is reported in the annual report at the General Meeting of Shareholders, furthermore, Article 1 paragraph (3) UUPT states TJSL is a commitment from the company to participate in a sustainable economic development that is useful for improving the quality of life and a beneficial environment for all stakeholders. As with this commitment, the company should have the desire to include one of the clauses regarding TJSL, one of which is in the deed of amendment to the company's articles of association, even though Article 15 of the Company Law does not regulate the existence of a component of environmental social responsibility. The legal issue in this paper is a conflict of norms in the Company Law which states an obligation and is in the form of a commitment, but does not become a component in the company's articles of association. The problem studied is why it is important for the TJSL clause to be included in the deed, and how the construction of the clause is, with the aim of knowing the importance and form of the calculus if included in the deed of amendment to the company's budget. This type of research leads to normative juridical, using statutory approaches, conceptual approaches through primary, secondary and tertiary legal materials. The results of this study with the inclusion of the TJSL clause can provide legal certainty in carrying out obligations, as a reminder (alarm) for the company, and the creation of legal order, the TJSL clause is either incorporated in the profit earning article or in a separate article on the deed of amendment to the articles of association either through the Partij deed (the parties) or Relaas deed (meeting minutes)